Menelusur Jejak Sejarah Perkembangan Penerbitan Buku Islam di Indonesia - KRISTYANTO, DIAN (Universitas Wijaya Kusuma Surabaya, 2019)
The publication of books about religion is now increasingly rapid, publishing Islamic books has been going on since the days of the classical and mid-Islamic world, where at that time science grew rapidly to enter developing countries such as Indonesia. The purpose of this article is to explore the historical history of the development of Islamic book publishing in Indonesia. The method used is library research. The development of Islamic literature in Indonesia began to boom around the 1970s. Many Islamic publications born at that time such as PT. Bulan Bintang, Gema Insani Press, PT. Al-Ma?arif, PT. Mizan Library and so on. In terms of appearance, the Islamic-themed books of the 1970s appeared to be classical in style, using newspaper and display tended to be less attractive, while publications after the 1980s appeared different because the books published looked more advanced, both in terms of their substance content, presentation style, as well as artistic. The conclusion is that Islamic education and publishers engaged in publishing Islamic books must have a strong bond in terms of the collaboration between the two countries, especially about the procurement of Islamic books needed by the community.